2010
DOI: 10.1021/ja1010724
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Orientational Order and Nonlinear Optical Response of the “Push−Pull” Chromophore RuPZn via Specific Incorporation into Densely Packed Monolayer Ensembles of an Amphiphilic 4-Helix Bundle Peptide: Second Harmonic Generation at High Chromophore Densities

Abstract: The macroscopic nonlinear optical response of the "push-pull" chromophore RuPZn incorporated into a single monolayer of the amphiphilic 4-helix bundle peptide (AP0) covalently attached to a solid substrate at high in-plane density has been measured. The second-order susceptibility, chi(zzz), was found to be in the range of approximately 15 x 10(-9) esu, consistent with a coherent sum of the nonlinear contributions from the individual chromophores (beta) as previously measured in isotropic solution through hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…When appropriately functionalized molecules are arranged in one-handed helices, they often display intriguing physical phenomena that never occur in centrosymmetric structures, as represented by second harmonic generation (SHG) 1 2 3 4 and piezoelectricity 5 6 7 8 . These helices would also give a clue to pursue unexplored predictions, including molecular solenoid effects 9 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When appropriately functionalized molecules are arranged in one-handed helices, they often display intriguing physical phenomena that never occur in centrosymmetric structures, as represented by second harmonic generation (SHG) 1 2 3 4 and piezoelectricity 5 6 7 8 . These helices would also give a clue to pursue unexplored predictions, including molecular solenoid effects 9 10 .…”
mentioning
confidence: 99%
“…To explore these phenomena further, a key issue is to improve the quality of their output signals. For this purpose, the most straightforward approach is to orient the helices macroscopically so that mutual cancellation of signals is prevented 3 4 5 6 8 . Although such hierarchical structures, realizing one-handed helicity and macroscopic orientation at the same time, are rarely obtained, their rational formation would become possible by using a framework with macroscopically oriented helical pores 11 12 13 14 15 16 17 .…”
mentioning
confidence: 99%
“…More recent studies have taken tilt distribution into account-Benninger et al (18) found hcos 2 4i and hcos 4 4i moments from 2PF images, but experimental imprecision left them unable to resolve a parameterized distribution function. In the study of a densely incorporated dye, Gonella et al (34) excluded particular distributions by combining SHG imaging with grazing-incidence x-ray diffraction, but were left with a range of possible distributions due to experimental constraints.…”
Section: Tilt-angle Intensity Functionsmentioning
confidence: 99%
“…In most cases, the long axis of the dye molecule can be assumed to be coincident with its transition dipole moment (TDM). Previously, studies that have quantified tilt angle have employed solid-state NMR (6)(7)(8), electron paramagnetic resonance (9,10), polarization coherent anti-Stokes Raman scattering (11), infrared dichroism (12)(13)(14)(15), polarization anisotropy fluorescence (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and secondharmonic generation (SHG) microscopy (11,(27)(28)(29)(30)(31)(32)(33)(34). Experimental data from these investigations have been complemented by computational methods for modeling molecules in membranes (8,(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of this “directed-assembly” approach was demonstrated using a dipolar chromophore possessing a large optical hyperpolarizability, since the macroscopic nonlinear optical (NLO) response of the 2-D ensemble is exquisitely sensitive to the degree of acentric order achieved. 24, 25 …”
Section: Introductionmentioning
confidence: 99%